2019
DOI: 10.1002/jsfa.9690
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rhizosphere bacterial community and berry quality of Hutai No.8 (Vitis vinifera L.) with different ages, and their relations

Abstract: BACKGROUND Rhizosphere soil microbial communities play an important role in grapevine growth. However, the relationship of the rhizosphere soil bacterial community and berry quality of Hutai No.8 grape with different tree‐ages is unclear. In this work, the Biolog‐ECO technique was used to explore the functional diversity of the rhizosphere soil bacterial communities of Hutai No.8 grape with five ages (3, 5, 7, 9 and 11 years old). Meanwhile, grape berry quality indicators related to berry appearance, flavor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some studies are focused on vineyard age and compare individual grapevines cultivated in the same plot as regards bacterial endophytes [70] , wood fungal pathogens [80] , stem fungi [81] , rhizosphere soil bacteria [82] , or AMF [56] . A positive correlation between grapevine age and the specific diversity of fungal endophytes has been demonstrated [81] .…”
Section: Factors Influencing the Microbiota In Healthy Grapevinesmentioning
confidence: 99%
“…Some studies are focused on vineyard age and compare individual grapevines cultivated in the same plot as regards bacterial endophytes [70] , wood fungal pathogens [80] , stem fungi [81] , rhizosphere soil bacteria [82] , or AMF [56] . A positive correlation between grapevine age and the specific diversity of fungal endophytes has been demonstrated [81] .…”
Section: Factors Influencing the Microbiota In Healthy Grapevinesmentioning
confidence: 99%
“…It has been shown that the age of the plant and its physiological status have a significant influence on the composition of rhizosphere bacteria [19,20]. Moreover, by manipulating cultivation techniques that influence the structure of the rhizosphere microbial community, it is possible to regulate the growth and development of fruit trees [21].…”
Section: Introductionmentioning
confidence: 99%
“…By using Biolog™ EcoPlates technology, Ji et al (2019) [ 44 ] showed a correlation between metabolic activities and functional diversity of rhizosphere microbial communities and physicochemical indices of grape berry quality. Association of grapevine with AMF facilitates the synthesis of plant secondary metabolites such as resveratrol, flavonol or anthocyanin, which improve berry quality and plant tolerance to environmental stresses [ 45 ].…”
Section: Close To the Roots A Dynamic Spot For Molecular Exchangementioning
confidence: 99%